MODEL PENINGKATAN KINERJA SDM MELALUI PROSEDURAL JUSTICE DAN KOMITMEN AFEKTIF DENGAN EFEK MODERASI SUPERVISI - Itut Anggraini Hendraningsih; Abdul Hakim (Jurnal Riset Bisnis Indonesia, 2016)
Puskesmas as the forefront of the basic health measures implementation. Puskesmas has anobligation to provide optimum service for the community. We often heard criticism and condemnationfrom various society to the system of health care in Puskesmas which are less professional andless empathy in implementing health care programs to the community. This explanatory researchexamines the influence of procedural justice and affective commitment to the performance of thehuman resources wuth the moderation effect of supervision in accredited Puskesmas in Jepara,Mlonggo, Welahan I, Welahan II. Using SEM PLS analytical system to examine 109 responden withsampling methode “sensus” This study procedural justice has a significant positive effect on affectivecommitment of human resources, procedural justice has no significant effect on the performance ofHR, affective commitment significant effect on the performance of human resources, supervisiondoes not moderate the relationship affective commitment and performance of human resources.This study has low value of R Square, where the variation of affective commitment can only bedescribed procedural justice by 20.6% while 79.4% is explained by variations in other variables notincluded in the model, and performance variation can be explained procedural justice and affectivecommitment amounted to 25.9%, while 74.1% of the variation is explained by other variables wichwere not included in the model so that it will be needed to include other dependent variables ascontrol variables to be able to describe the problem.Keywords: prosedural justice, supervision, affective commitment, and human resourcesperformance.